Implementation of Educational and Ethical Awareness Programs through Internal Control and Whistleblowing Systems to Prevent Fraud in the Traffic Unit of Bandar Lampung Police - Novi Indah Earlyanti; Alfahry Rasman (Yayasan Adra Karima Hubbi, 2026)
Fraud prevention efforts cannot be separated from the methods that can be done to eliminate the opportunity for fraud, including having a good internal control system and implementing an adequate whistleblowing system. Therefore, this study aims to analyze the effect of the internal control system and whistleblowing system on preventing fraud by members of the Bandar Lampung Police Traffic Unit (Satlantas). This study uses a quantitative approach with a survey method conducted on 78 members of the Bandar Lampung Police Traffic Unit. Data analysis techniques used include instrument testing, classical assumption testing, and multiple linear regression hypothesis testing. The results of this study obtained a regression equation, namely Y ? = 5.902 + 0.036 X1 + 0.859 X2 + e. This study concludes that partially, the internal control system does not have a significant effect on preventing fraud by members of the Bandar Lampung Police Traffic Unit, while the whistleblowing system has a significant effect on preventing fraud by members of the Bandar Lampung Police Traffic Unit. Simultaneously, the internal control system and whistleblowing system have a significant influence on the prevention of fraud by members of the Bandar Lampung Police Traffic Unit with a contribution of 70.7% while the remaining 29.3% is influenced by other variables.